Plagiarism of Scientific Works Viewed from the Perspective of Criminal Law in Indonesia - Mulyanto; Wibawa, Iskandar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The rise in acts of plagiarism of scientific work occurs due to a lack of awareness and understanding of students and academics about the ethics of scientific writing and the consequences of these actions. This research aims to describe the criteria for acts of plagiarism, legal sanctions for acts of plagiarism, efforts to resolve disputes over violations of acts of plagiarism, and strategies for preventing plagiarism in higher education. Type of normative juridical research with a statutory approach. Primary data sources include statutory regulations such as Regulation of the Minister of National Education of the Republic of Indonesia Number 17 of 2010 concerning Prevention and Management of Plagiarism in Higher Education, and Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. Secondary data consists of research journals concerned with the legal issue of plagiarism. The research results show that the act of taking or using someone else's creative work without stating the source appropriately and adequately is considered plagiarism. Acts of plagiarism can be subject to administrative sanctions or criminal sanctions. Administrative sanctions include warnings, written warnings, and cancellation of diplomas, while criminal sanctions include imprisonment for a certain period of time and a fine. If an act of plagiarism has occurred, an attempt can be made to resolve it through mediation, but if it cannot be resolved through mediation, then criminal action can be taken. Efforts to prevent plagiarism of scientific works in higher education are carried out through plagiarism-free statements, open access publication of scientific works, and administrative sanctions.